COMMUNICATION AND MARKET SHARING: AN EXPERIMENT ON THE EXCHANGE OF SOFT AND HARD INFORMATION. (28th September 2020) - Freitag, Andreas; Roux, Catherine; Thöni, Christian
Abstract: We study the role of communication in collusive market sharing. In a series of Cournot oligopoly experiments with multiple markets, we vary the information that firms can exchange: hard information—verifiable information about past conduct—and soft information—unbinding information about future conduct. We find that the effect of communication on the firms' ability to collude depends on the type of information available: Whereas market prices increase only slightly with hard information, the price raise due to soft information is substantial. Our results point to the types and contents of communication that should be of particular concern to antitrust authorities.